A combination of the immunotherapeutic drug anti-programmed death 1 with lenalidomide enhances specific T cell immune responses against acute myeloid Leukemia cells - Guinn, Barbara; Schuler, Patrick; Schrezenmeier, Hubert; Hofmann, Susanne; Weiss, Johanna; Bulach, Christiane; Götz, Marlies; Greiner, Jochen (International journal of molecular sciences, 2023)
Immune checkpoint inhibitors can block inhibitory molecules on the surface of T cells, switching them from an exhausted to an active state. One of these inhibitory immune checkpoints, programmed cell death protein 1 (PD-1) is expressed on T cell subpopulations in acute myeloid leukemia (AML). PD-1 expression has been shown to increase with AML progression following allo-haematopoeitic stem cell transplantation, and therapy with hypomethylating agents. We have previously shown that anti-PD-1 can enhance the response of leukemia-associated antigen (LAA)-specific T cells against AML cells as well as leukemic stem and leukemic progenitor cells (LSC/LPCs) ex vivo. In concurrence, blocking of PD-1 with antibodies such as nivolumab has been shown to enhance response rates post-chemotherapy and stem cell transplant. The immune modulating drug lenalidomide has been shown to promote anti-tumour immunity including anti-inflammatory, anti-proliferative, pro-apoptotic and anti-angiogenicity. The effects of lenalidomide are distinct from chemotherapy, hypomethylating agents or kinase inhibitors, making lenalidomide an attractive agent for use in AML and in combination with existing active agents. To determine whether anti-PD-1 (nivolumab) and lenalidomide alone or in combination could enhance LAA-specific T cell immune responses, we used colony-forming immune and ELISpot assays. Combinations of immunotherapeutic approaches are believed to increase antigen-specific immune responses against leukemic cells including LPC/LSCs. In this study we used a combination of LAA-peptides with the immune checkpoint inhibitor anti-PD-1 and lenalidomide to enhance the killing of LSC/LPCs ex vivo. Our data offer a novel insight into how we could improve AML patient responses to treatment in future clinical studies.